On the Riesz Means of Expansions by Riesz Bases Formed by Eigenfunctions for the Ordinary Differential Operator of 4-th Order - Tahir, M. B.; Aswhad, A. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The aim of this paper is prove a theorem on the Riesz mean of expansions with respect to Riesz bases, which extends the previous results of Loi and Tahir on the Schrodinger operator to the operator of 4-th order.